Pengaruh Tiga Taraf Masukan terhadap Beberapa Varietas Kedelai di Lahan Kering Masam di Daerah Tandun Provinsi Riau (Jurnal Agro Teknologi Tropika, 2014)
To get good productivity, the management of dryland in acid soil require specific technologies that made farmingmore effective, efficient and sustainable. Riau province has potential for crop agriculture, with the majority of plantationcrops and apart of food crops such as upland rice, soy, peanuts and corn.. The purpose of this study is to study severalvarieties of soybean response to three levels of inputs in dry land areas Tandun Riau province. The experimental designused is a randomized block design with two factors. The first factor is the level of input that consists of a). A low input (50kg.ha-1 urea, 50 kg.ha-1 SP-36, 50 kg.ha-1 KCl); b) Medium input (75 kg.ha-1 urea, 100 kg.ha-1 SP-36, 75 kg.ha-1 KCl and500 kg.ha-1 lime); c) High input (75 kg.ha-1 urea, 100 kg.ha-1 SP-36, 100 kg.ha-1 KCl and 1000 kg.ha-1 lime. Factor II issoybean varieties that consist of a). Anjasmoro, b). Agromulyo, c). Tanggamus, d). Kaba and e). Wilis. Observationsincluded plant height, number of branches, number of empty pods per plant, number of pods per plant and pod yield. Thestudy shows the input level and variety affect the number of branches, number of empty pods, number of pods and soybeanyields. Anjasmoro varieties with high input gives the highest yield (1.5 t.ha-1) when compared to other treatmentcombinations. While the lowest yield was obtained at Kaba and Wilis varieties with low input, ie, 0.8 t.ha-1.Keywords: varieties, soybeans, input level, sour dry land